Intervention to Reduce Burnout Among Nurses: A Scoping Review - Lestari, Putu Indah Jelita Lestari; Swarjana, I Ketut; Adianta, I Ketut Alit; Sutini, Ni Kadek (Babali Nursing Research, 2026)
Background: Burnout among operating room nurses negatively affects patient safety and quality of care, highlighting the need for effective and accessible interventions in high-intensity clinical environments. Digital media–based relaxation approaches, particularly smartphone video interventions, offer a low-cost, flexible, and scalable solution. Therefore, this scoping review aims to map and synthesize the existing evidence on interventions to reduce burnout among nurses, with a particular focus on digital relaxation strategies delivered through smartphone videos. Methods: This literature review examined previous research findings in published articles. Article searches were conducted through PubMed and Science Direct using the keywords "Burnout interventions and treatment" for English-language articles and "burnout interventions AND treatment" for Indonesian-language articles. Fifteen articles were extracted based on the inclusion criteria. Results: Of the 313 identified articles (271 PubMed; 42 ScienceDirect), 308 were screened after removing duplicates; 50 were read in full; and 15 studies were included. The majority reported a reduction in burnout or its components (emotional exhaustion and depersonalization) and/or an improvement in professional quality of life following the intervention. Technology-based interventions (video/smartphone, mHealth, SMS) have demonstrated consistent effects and ease of implementation; however, the heterogeneity of instruments and monitoring duration limits generalizability. Conclusion: The review indicates that digital and smartphone-based relaxation interventions effectively reduce burnout levels among nurses, particularly in high-stress environments such as operating rooms. These methods are flexible, accessible, and cost-effective, making them a promising complementary strategy for burnout management. However, differences in study design, instruments, and intervention duration suggest a need for more standardized and longitudinal research to ensure sustainable and generalizable outcomes.